Nietzsche and Islam - Jackson, Roy 1962- (Routledge advances in Middle East and Islamic studies, 2007)
In the light of the 'post September 11th' debates with focus on aspects of the 'clash of civilisation' thesis, the issue of Islamic identity is a crucial one. This book provides an insight into Friedrich Nietzsche's views on religion and shows that his philosophy can make an important contribution to what is considered to be Islam's key paradigms